Psychological Issues In Covid 19 Outbreak - Ayurvedic Approach - Sanker, Vidhya M; Madhvan, Jithesh (Asian Journal of Pharmaceutical Research and Development, 2020)
Corona Virus Disease (COVID-19) is a newly revealed infectious disease declared as pandemic by WHO. Through its fast spreading nature it created an alarming situation throughout the globe. The only possible way to control the spread is to break the chain of transmission by keeping social distancing along with maintaining strict personal hygiene. A complete lockdown was the effective method chosen by the authorities in such a situation. The panic situation created by the disease along with the unfamiliar way of conduct imposed several psychological impacts on human life. Many can’t cope up with the situation on their own and are in need of an intervention such as Psychological First Aid. Fear, anxiety, future concerns, interpersonal relationships issues, behavioural issues, domestic abuses, separation anxiety are a few among the psychological issues reported. A well explained modality of psychotherapy mentioned in Ayurveda i.e; Satvavajaya chikitsa can be adopted in such situations. Jnana (knowledge of self), Vijnana (scientific reasoning), Dhairya (determination or patience), Smrithi (application of recollections or memory) and Samadhi (attaining a stable state of mind) are the steps of this management which are applicable in any psychological issues, including that resulting from COVID as well. Considering the severity of the symptoms, medical management can also be recommended. By adopting such measures mentioned in the Ayurvedic science, we can hope to provide relief to the affected and also to help them to physical and mental wellbeing.